EXPLORATION OF FACTORS AFFECTING RURAL ENTERPRISING WOMEN IN LIBODE, EASTERN CAPE - Dlakavu, Nandipha (My University, 2011)
The research interrogates the trajectories of rural enterprises since many are in peripheral areas and are still lagging behind in terms of advancement. Through examining existing literature and by employing rigorous and participatory fieldwork including questionnaires, focus group interviews as well as key informant discussions, challenges confronting rural enterprising women were conceptualised. The findings reveal that domestic dynamics and cultural ideology obstruct entry into self-employment. Concomitantly, the study discovered that there are a variety of institutional factors influencing women's access to labour markets. Although it is envisaged that it would be a while and difficult for some of the challenges to be overcome as there is no magic wand for these problems, tentative recommendations are suggested for government interventions that would lead to the empowerment of rural women. The study recommends proactive strategies that can minimise constraints on the entrepreneurial rural activities and provide the women with suitable business related services. The research is informed by the realisation that capacity building is important for the achievement of improved socio-economic practices among rural communities
MM - P&DM
Keywords: Rural enterprises; Women; Self-employment